A composite styrene-acrylic emulsion surface sizing agent and preparation method thereof

By preparing the composite styrene acrylic emulsion surface sizing agent, using components such as core-shell microspheres and silane coupling agents to form a dense structure, the problem of poor water resistance in the prior art is solved, and the water resistance and ring pressure of the paper are significantly improved strength.

CN118668522BActive Publication Date: 2024-12-24NANTONG TENGLONG CHEM TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410785767.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-18
Publication Date
2024-12-24
Estimated Expiration
2044-06-18

AI Technical Summary

Technical Problem

In the prior art, the water resistance of the surface glue agent is poor and cannot effectively improve the water resistance of the paper.

Method used

Using composite styrene acrylic emulsion surface sizing agent, core-shell microspheres A and core-shell microspheres B are prepared, and silane coupling agent and hydrophobic long-chain alkyl monomer are added to the system to form a dense mesh structure to enhance the paper. water resistance and ring pressure strength.

Benefits of technology

It significantly improves the water resistance and ring compressive strength of the paper, reduces the amount of styrene, and enhances the mechanical strength and fold resistance of the paper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of sizing agent preparation, and in particular to a composite styrene-acrylic emulsion surface sizing agent and a preparation method thereof. The surface sizing agent is prepared from the following raw materials in parts by mass: 20-30 parts of core-shell microspheres A, 10-15 parts of core-shell microspheres B, 3-5 parts of silane coupling agents, 8-12 parts of hydrophobic long-chain alkyl monomers, 2-4 parts of initiators, 2-5 parts of aluminum sulfate solutions, and 50-60 parts of deionized water. The invention compounds the core-shell microspheres A and the core-shell microspheres B, and introduces the silane coupling agent and the hydrophobic long-chain alkyl monomer into the system, wherein the core-shell microspheres A can improve the ring crush strength of paper and reduce the occurrence of paper becoming brittle, and the core-shell microspheres B with smaller particle sizes are filled in the gaps of the core-shell microspheres A to prevent water from penetrating, and the silane coupling agent and the hydrophobic long-chain alkyl monomer are added to further improve the water resistance and the ring crush strength of the paper. Therefore, the composite styrene-acrylic emulsion surface sizing agent has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sizing agent preparation, in particular to a composite styrene-acrylic emulsion surface sizing agent and a preparation method thereof. Background Art

[0002] In recent years, with the continuous improvement of requirements for paper surface quality, mechanical properties, printing adaptability, etc., surface sizing agent product technology has been further developed and applied. After the surface sizing agent is sized or coated on the paper surface, the polymer molecules penetrate into the gaps between the paper fibers, which can not only enhance the adsorption effect on the paper fibers and fill the gaps between the paper fibers, having a good sizing (retention) effect, but also delay the penetration and diffusion of fluids between paper fibers, thereby improving the paper's gloss, tensile strength, water resistance, burst resistance, folding resistance and other properties.

[0003] Currently, the surface sizing agents for papermaking developed and applied in China mainly include water-soluble polymer surface sizing agents, polymer aqueous dispersion surface sizing agents, and polyacrylate emulsion surface sizing agents. Conventional polyacrylate emulsion surface sizing agents have excellent sizing properties and are significantly superior to other resin emulsion surface sizing agents in terms of synthesis conditions, adhesion, and raw material sources. However, they are generally unable to undergo post-crosslinking, resulting in poor sizing properties. Patented technical document CN115627655A discloses a method for preparing an air-drying, oil-modified, amphoteric polyacrylate emulsion surface sizing agent. This invention prepares a bio-based monomer a using linoleic acid and allyl glycerol ester as raw materials, and a bio-based monomer b using linoleic acid and glycidyl methacrylate as raw materials. An air-drying oil-modified amphoteric polyacrylate polymer emulsifier is prepared using RAFT epoxy resin, bio-based monomer a, dimethylaminoethyl methacrylate, styrene, chloroacetic acid, etc. as raw materials. The emulsifier is then used in emulsion polymerization using bio-based monomer a, bio-based monomer b, isobutyl methacrylate, butyl acrylate, and hydroxypropyl acrylate as raw materials to prepare an emulsion. However, the emulsion provided by this method has poor water resistance for paper. Therefore, the patent technology document with publication number CN116217814A discloses a core-shell structure surface sizing agent and a preparation method thereof. This invention prepares a surface sizing agent with a core-shell structure by introducing an organosiloxane into the system. However, the improvement of the water resistance of paper by the sizing agent obtained by this method is relatively limited.

[0004] Therefore, according to the above-mentioned related technologies, it is urgent to develop a composite styrene-acrylic emulsion surface sizing agent and a preparation method thereof. Summary of the Invention

[0005] In view of this, the object of the present invention is to provide a composite styrene-acrylic emulsion surface sizing agent and a preparation method thereof, so as to solve the problem of poor water resistance of the sizing agent in the prior art.

[0006] Based on the above purpose, the present invention provides a composite styrene-acrylic emulsion surface sizing agent and a preparation method thereof.

[0007] A composite styrene-acrylic emulsion surface sizing agent is prepared from the following raw materials in parts by weight: 20-30 parts of core-shell microspheres A, 10-15 parts of core-shell microspheres B, 3-5 parts of a silane coupling agent, 8-12 parts of a hydrophobic long-chain alkyl monomer, 2-4 parts of an initiator, 2-5 parts of an aluminum sulfate solution, and 50-60 parts of deionized water;

[0008] The ratio of the particle size of the core-shell microspheres A to the particle size of the core-shell microspheres B is 2-3:1;

[0009] The core-shell microspheres A are core-shell microspheres with styrene-methyl methacrylate copolymer as the core and butyl acrylate-acrylamide copolymer as the shell;

[0010] The core-shell microspheres B are butyl acrylate-acrylamide copolymer microspheres.

[0011] Preferably, the preparation method of the core-shell microspheres A is as follows:

[0012] Step A1. Styrene, methyl acrylate, sodium lauryl sulfate, and nonylphenoloxyethylene ether were dissolved in deionized water and pre-emulsified at room temperature with high-speed stirring to obtain a core layer pre-emulsion. Sodium bicarbonate and potassium persulfate were added and reacted at 75-80°C for 40-50 minutes to obtain a seed emulsion.

[0013] Step A2. Butyl acrylate, acrylamide, sodium lauryl sulfate and nonylphenol oxyethylene ether were dissolved in deionized water and pre-emulsified at room temperature with high-speed stirring to obtain a shell pre-emulsion. Sodium bicarbonate and potassium persulfate were then added and reacted at 70-75°C for 40-50 minutes.

[0014] Step A3. The seed emulsion is heated to 75-80°C, and the shell pre-emulsion and potassium persulfate are added. After the addition is complete, triethanolamine is added to adjust the pH to 6.5-7.5. The mixture is reacted at 75-80°C for 4-5 hours. The resulting suspension product is washed 3-5 times with 0.5 mol / L dilute hydrochloric acid and then washed with deionized water until neutral to obtain core-shell microspheres A.

[0015] Preferably, the mass ratio of styrene, methyl acrylate, sodium lauryl sulfate, nonylphenoloxyethylene ether, deionized water, sodium bicarbonate and potassium persulfate in step A1 is 2-3:1-1.25:1.5-2:0.8-1:140-150:0.4-0.5:0.5-0.6.

[0016] Preferably, the mass ratio of butyl acrylate, acrylamide, sodium lauryl sulfate, nonylphenoloxyethylene ether, deionized water, sodium bicarbonate and potassium persulfate in step A2 is 1-1.2:2-2.5:1.5-2:0.8-1.2:140-150:0.4-0.5:0.5-0.6.

[0017] Preferably, in step A3, the mass ratio of the seed emulsion, the shell pre-emulsion and potassium persulfate is 10-15:10-15:0.8-1.3.

[0018] Preferably, the preparation method of the core-shell microspheres B is as follows:

[0019] Step B1. Sodium hydroxide and sodium chloride were dissolved in deionized water to obtain phase A, and 1 wt.% sodium lauryl sulfate solution, magnesium chloride and sodium nitrite were dissolved in deionized water to obtain phase B;

[0020] Step B2. Phase B was added to phase A by a peristaltic pump at a speed of 65-75 rpm, and then 0.5 mol / L dilute sulfuric acid solution was added, and the pH was adjusted to 9.5-10.5 to obtain a magnesium hydroxide dispersion;

[0021] Step B3 butyl acrylate, acrylamide, benzoyl peroxide and polyethylene glycol dimethacrylate were blended as phase C, phase C was added to the magnesium hydroxide dispersion, and homogenized with a high-speed shear emulsifier to obtain a stable suspension;

[0022] Step B4. The suspension was reacted at 70-75°C for 15-20h, and then aged at 80°C for 1.5-2h. The resulting suspension product was washed 3-5 times with 0.5 mol / L dilute hydrochloric acid and then washed with deionized water until neutral to obtain core-shell microspheres B.

[0023] Preferably, the mass ratio of sodium hydroxide, sodium chloride and deionized water in phase A in step B1 is 1:1:10, the mass ratio of 1 wt.% sodium lauryl sulfate solution, magnesium chloride, sodium nitrite and deionized water in phase B in step B1 is 2:1:1:10, and the mass ratio of phase A and phase B in step B2 is 1:1.

[0024] Preferably, the mass ratio of butyl acrylate, acrylamide, benzoyl peroxide, polyethylene glycol dimethacrylate and magnesium hydroxide dispersion in step B3 is 2-2.5:1.3-1.8:0.6-0.8:0.3-0.5:8-10.

[0025] Preferably, the silane coupling agent is any one of tetraethyl orthosilicate, methyltriethoxysilane and ethyltriethoxysilane.

[0026] The hydrophobic long-chain alkyl monomer is any one of octadecyl methacrylate, hexadecyl methacrylate and dodecyl methacrylate.

[0027] Preferably, the initiator is any one of benzoyl peroxide, potassium persulfate and ammonium persulfate, and the concentration of the aluminum sulfate solution is 35%-40%.

[0028] A method for preparing a composite styrene-acrylic emulsion surface sizing agent comprises the following steps:

[0029] Step S1. core-shell microspheres A, core-shell microspheres B, a silane coupling agent, a hydrophobic long-chain alkyl monomer, an initiator, and deionized water are uniformly mixed and reacted at 70-75° C. for 30-35 minutes to obtain a polymer emulsion;

[0030] Step S2: adding aluminum sulfate solution to the polymer emulsion to obtain a composite styrene-acrylic emulsion surface sizing agent.

[0031] Beneficial effects of the present invention:

[0032] The harder styrene-methyl methacrylate copolymer core in the core-shell microspheres A provided by the present invention can improve the ring crush strength of paper, while the softer acrylate-acrylamide copolymer shell coated on the surface of the core can reduce the brittleness of paper caused by the addition of styrene.

[0033] The core-shell microspheres B provided by the present invention have a small particle size and can be filled in the gaps of the core-shell microspheres A to prevent moisture from penetrating into the interior of the paper, thereby reducing the amount of styrene used and increasing the water resistance of the paper. In addition, the core-shell microspheres B will form bonds with active groups inside the system and on the surface of the paper, further increasing the water resistance and ring crush strength of the paper.

[0034] The present invention adds a silane coupling agent and a hydrophobic long-chain alkyl monomer into the system. The compounding of the silane coupling agent and the hydrophobic long-chain alkyl monomer can further increase the water resistance and ring crush strength of paper. Therefore, the composite styrene-acrylic emulsion surface sizing agent prepared by the present invention has broad application prospects. DETAILED DESCRIPTION

[0035] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to specific embodiments.

[0036] Example 1: A method for preparing a composite styrene-acrylic emulsion surface sizing agent, comprising the following steps:

[0037] Step S1. 2 g of styrene, 1 g of methyl acrylate, 1.5 g of sodium lauryl sulfate, and 0.8 g of nonylphenoloxyethylene ether were dissolved in 140 g of deionized water, and pre-emulsified at room temperature with high-speed stirring to obtain a core layer pre-emulsion. 0.4 g of sodium bicarbonate and 0.5 g of potassium persulfate were added, and the mixture was reacted at 75°C for 40 min to obtain a seed emulsion.

[0038] Step S2. 1 g of butyl acrylate, 2 g of acrylamide, 1.5 g of sodium lauryl sulfate, and 0.8 g of nonylphenoloxyethylene ether were dissolved in 140 g of deionized water, and pre-emulsified at room temperature with high-speed stirring to obtain a shell pre-emulsion. 0.4 g of sodium bicarbonate and 0.5 g of potassium persulfate were then added, and the mixture was reacted at 70°C for 40 min.

[0039] Step S3. Heat 10 g of seed emulsion to 75°C, add 10 g of shell pre-emulsion and 0.8 g of potassium persulfate, add triethanolamine after the addition is complete to adjust the pH to 6.5, react at 75°C for 4 h, wash the resulting suspension product with 0.5 mol / L dilute hydrochloric acid three times, and then wash with deionized water until neutral to obtain core-shell microspheres A.

[0040] Step S4. 1 g of sodium hydroxide and 1 g of sodium chloride were dissolved in 10 g of deionized water to obtain phase A. 2 g of 1 wt.% sodium lauryl sulfate solution, 1 g of magnesium chloride, and 1 g of sodium nitrite were dissolved in 10 g of deionized water to obtain phase B.

[0041] Step S5. 12 g of phase B was added to 12 g of phase A by a peristaltic pump at a speed of 65 rpm, and then a 0.5 mol / L dilute sulfuric acid solution was added and the pH was adjusted to 9.5 to obtain a magnesium hydroxide dispersion;

[0042] Step S6. 2 g of butyl acrylate, 1.3 g of acrylamide, 0.6 g of benzoyl peroxide, and 0.3 g of polyethylene glycol dimethacrylate were blended as phase C, and phase C was added to 8 g of magnesium hydroxide dispersion and homogenized using a high-speed shear emulsifier to obtain a stable suspension;

[0043] Step S7. The suspension was reacted at 70°C for 15 h and then aged at 80°C for 1.5 h. The resulting suspension was washed three times with 0.5 mol / L dilute hydrochloric acid and then washed with deionized water until neutral to obtain core-shell microspheres B, wherein the particle size ratio of core-shell microspheres A to core-shell microspheres B was 2:1.

[0044] Step S8. 20 g of core-shell microspheres A, 10 g of core-shell microspheres B, 3 g of tetraethyl orthosilicate, 8 g of octadecyl methacrylate, 2 g of benzoyl peroxide, and 50 g of deionized water were mixed and reacted at 70° C. for 30 min to obtain a polymer emulsion;

[0045] Step S9. Add 2 g of 35% aluminum sulfate solution to the polymer emulsion to obtain a composite styrene-acrylic emulsion surface sizing agent.

[0046] Example 2: A method for preparing a composite styrene-acrylic emulsion surface sizing agent, comprising the following steps:

[0047] Step S1. 2.5 g of styrene, 1.15 g of methyl acrylate, 1.7 g of sodium lauryl sulfate, and 0.9 g of nonylphenoloxyethylene ether were dissolved in 145 g of deionized water, and pre-emulsified at room temperature with high-speed stirring to obtain a core layer pre-emulsion. 0.45 g of sodium bicarbonate and 0.55 g of potassium persulfate were added, and the mixture was reacted at 77°C for 45 min to obtain a seed emulsion.

[0048] Step S2. 1.1 g of butyl acrylate, 2.2 g of acrylamide, 1.8 g of sodium lauryl sulfate, and 1 g of nonylphenoloxyethylene ether were dissolved in 145 g of deionized water and pre-emulsified at room temperature with high-speed stirring to prepare a shell pre-emulsion. 0.45 g of sodium bicarbonate and 0.55 g of potassium persulfate were then added and reacted at 73°C for 45 min.

[0049] Step S3. 13 g of the seed emulsion was heated to 78°C, 13 g of the shell pre-emulsion and 1 g of potassium persulfate were added, and after the addition was complete, triethanolamine was added to adjust the pH to 7. The mixture was reacted at 77°C for 4.5 h. The resulting suspension was washed four times with 0.5 mol / L dilute hydrochloric acid and then washed with deionized water until neutral to obtain core-shell microspheres A.

[0050] Step S4. 1 g of sodium hydroxide and 1 g of sodium chloride were dissolved in 10 g of deionized water to obtain phase A. 2 g of 1 wt.% sodium lauryl sulfate solution, 1 g of magnesium chloride, and 1 g of sodium nitrite were dissolved in 10 g of deionized water to obtain phase B.

[0051] Step S5. 12 g of phase B was added to 12 g of phase A by a peristaltic pump at a speed of 70 rpm, and then a 0.5 mol / L dilute sulfuric acid solution was added and the pH was adjusted to 10 to obtain a magnesium hydroxide dispersion;

[0052] Step S6. 2.3 g of butyl acrylate, 1.6 g of acrylamide, 0.7 g of benzoyl peroxide, and 0.4 g of polyethylene glycol dimethacrylate were blended as phase C, and phase C was added to 9 g of magnesium hydroxide dispersion and homogenized using a high-speed shear emulsifier to obtain a stable suspension;

[0053] Step S7. The suspension was reacted at 73°C for 17 h and then aged at 80°C for 1.7 h. The resulting suspension was washed four times with 0.5 mol / L dilute hydrochloric acid and then washed with deionized water until neutral to obtain core-shell microspheres B, wherein the particle size ratio of core-shell microspheres A to core-shell microspheres B was 2.5:1.

[0054] Step S8. 25 g of core-shell microspheres A, 13 g of core-shell microspheres B, 4 g of methyltriethoxysilane, 10 g of hexadecyl methacrylate, 3 g of potassium persulfate, and 55 g of deionized water were mixed and reacted at 73° C. for 33 min to obtain a polymer emulsion;

[0055] Step S9. Add 4 g of 38% aluminum sulfate solution to the polymer emulsion to obtain a composite styrene-acrylic emulsion surface sizing agent.

[0056] Example 3: A method for preparing a composite styrene-acrylic emulsion surface sizing agent, comprising the following steps:

[0057] Step S1. 3 g of styrene, 1.25 g of methyl acrylate, 2 g of sodium lauryl sulfate, and 1 g of nonylphenoloxyethylene ether were dissolved in 150 g of deionized water, and pre-emulsified at room temperature with high-speed stirring to obtain a core layer pre-emulsion. 0.5 g of sodium bicarbonate and 0.6 g of potassium persulfate were added, and the mixture was reacted at 80°C for 50 min to obtain a seed emulsion.

[0058] Step S2. 1.2 g of butyl acrylate, 2.5 g of acrylamide, 2 g of sodium lauryl sulfate, and 1.2 g of nonylphenoloxyethylene ether were dissolved in 150 g of deionized water and pre-emulsified at room temperature with high-speed stirring to prepare a shell pre-emulsion. 0.4-0.45-0.5 g of sodium bicarbonate and 0.6 g of potassium persulfate were then added and reacted at 75°C for 50 min.

[0059] Step S3. 15 g of seed emulsion was heated to 80°C, 15 g of shell pre-emulsion and 1.3 g of potassium persulfate were added, and after the addition was complete, triethanolamine was added to adjust the pH to 7.5. The mixture was reacted at 80°C for 5 h. The resulting suspension was washed five times with 0.5 mol / L dilute hydrochloric acid and then washed with deionized water until neutral to obtain core-shell microspheres A.

[0060] Step S4. 1 g of sodium hydroxide and 1 g of sodium chloride were dissolved in 10 g of deionized water to obtain phase A. 2 g of 1 wt.% sodium lauryl sulfate solution, 1 g of magnesium chloride, and 1 g of sodium nitrite were dissolved in 10 g of deionized water to obtain phase B.

[0061] Step S5. 12 g of phase B was added to 12 g of phase A by a peristaltic pump at a speed of 75 rpm, and then a 0.5 mol / L dilute sulfuric acid solution was added to adjust the pH to 10.5 to obtain a magnesium hydroxide dispersion;

[0062] Step S6. 2.5 g of butyl acrylate, 1.8 g of acrylamide, 0.8 g of benzoyl peroxide, and 0.5 g of polyethylene glycol dimethacrylate were blended as phase C, and phase C was added to 10 g of magnesium hydroxide dispersion and homogenized using a high-speed shear emulsifier to obtain a stable suspension;

[0063] Step S7. The suspension was reacted at 75°C for 20 h, and then aged at 80°C for 2 h. The resulting suspension was washed five times with 0.5 mol / L dilute hydrochloric acid and then washed with deionized water until neutral to obtain core-shell microspheres B, wherein the particle size ratio of core-shell microspheres A to core-shell microspheres B was 3:1.

[0064] Step S8. 30 g of core-shell microspheres A, 15 g of core-shell microspheres B, 5 g of ethyltriethoxysilane, 12 g of dodecyl methacrylate, 4 g of ammonium persulfate, and 60 g of deionized water were mixed and reacted at 75° C. for 35 min to obtain a polymer emulsion;

[0065] Step S9. Add 5 g of 40% aluminum sulfate solution to the polymer emulsion to obtain a composite styrene-acrylic emulsion surface sizing agent.

[0066] Comparative Example 1:

[0067] Compared with Example 1, this comparative example only replaces "core-shell microspheres A" with "core-shell microspheres B", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a composite styrene-acrylic emulsion surface sizing agent is obtained.

[0068] Comparative Example 2:

[0069] Compared with Example 1, this comparative example only replaces "core-shell microspheres B" with "core-shell microspheres A", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a composite styrene-acrylic emulsion surface sizing agent is obtained.

[0070] Comparative Example 3:

[0071] Compared with Example 1, this comparative example only replaces "the particle size ratio of core-shell microspheres A and core-shell microspheres B is 2:1" with "the particle size ratio of core-shell microspheres A and core-shell microspheres B is 1:2", and the remaining steps and parameters are the same. This comparative example will not be repeated, and finally a composite styrene-acrylic emulsion surface sizing agent is obtained.

[0072] Comparative Example 4:

[0073] Compared with Example 1, this comparative example does not add "silane coupling agent" during the preparation process of the composite styrene acrylic emulsion surface sizing agent. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a composite styrene acrylic emulsion surface sizing agent is obtained.

[0074] Comparative Example 5:

[0075] Compared with Example 1, this comparative example did not add "hydrophobic long-chain alkyl monomer" during the preparation of the composite styrene-acrylic emulsion surface sizing agent. The remaining steps and parameters were the same and will not be repeated in this comparative example. Finally, a composite styrene-acrylic emulsion surface sizing agent was obtained.

[0076] Comparative Example 6:

[0077] Compared with Example 1, this comparative example only replaces the "core-shell microspheres A" with an equal amount of "styrene-methyl methacrylate-butyl acrylate-acrylamide copolymer". The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a composite styrene-acrylic emulsion surface sizing agent is obtained.

[0078] Comparative Example 7:

[0079] Compared with Example 1, this comparative example only replaces the "core-shell microspheres B" with an equal amount of "butyl acrylate-acrylamide copolymer", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a composite styrene-acrylic emulsion surface sizing agent is obtained.

[0080] Performance testing:

[0081] Polymer latex film water resistance test:

[0082] Spray a small amount of release agent on a clean surface dish in advance, bake briefly to remove a small amount of solvent, then take an appropriate amount of emulsion in a culture dish, place it in an oven, and continuously increase the temperature stepwise to evaporate the water in the emulsion to form a latex film. The prepared latex film is wiped with anhydrous ethanol to remove the attached release agent, weighed and recorded as m0, and finally immersed in water. After 48 hours, take it out, wipe off the water and weigh it again, recorded as m1. The water absorption rate of each group of samples is calculated using the following formula:

[0083] ;

[0084] Water resistance test of polymer emulsion sized paper:

[0085] The water resistance of each group of sized paper samples was tested: the sizing agents synthesized in Examples 1 to 3 and Comparative Examples 1 to 7 were applied to filter paper for simple sizing. The time it took for a water droplet dropped on the surface of each group of sized paper to penetrate the paper was recorded. Five groups were tested in parallel, and different locations on the filter paper were selected for testing. The average value was recorded as the penetration time.

[0086] Determination of paper ring crush strength:

[0087] Refer to GB / T2679.8-2016 "Determination of Ring Compression Strength of Paper and Board", calculate the ring compression strength of sized paper R=F / l, where F is the pressure value (N) and l is the sample length (m). The sample cutting length of this experiment is 0.152m. The ring compression strength index Rd=R / G, the unit is N·m·g -1 , the results are shown in Table 1 below:

[0088] Table 1 Summary of test results of samples of Examples 1 to 3 and Comparative Examples 1 to 7

[0089]

[0090] Data Analysis:

[0091] As can be seen from Table 1, the sized paper obtained by the composite styrene acrylic emulsion surface sizing agent in Examples 1 to 3 has a lower water absorption rate, a longer penetration time and a higher ring crush strength index, which indicates that the sized paper obtained by the composite styrene acrylic emulsion surface sizing agent prepared by the present invention has good water resistance and high mechanical strength.

[0092] This may be because the core-shell microspheres B provided by the present invention have a smaller particle size, which can be filled in the gaps of the core-shell microspheres A to prevent moisture from penetrating into the interior of the paper, thereby reducing the amount of styrene used and increasing the water resistance of the paper. In addition, the silane coupling agent and the hydrophobic long-chain alkyl monomer added to the system are compounded and synergistic. On the one hand, the silane coupling agent is adsorbed on the surfaces of the core-shell microspheres A and B due to electrostatic effects to promote bonding between them and the paper. On the other hand, since the silane coupling agent itself forms oligomers, when applied to the surface of the paper, it can be effectively adsorbed on the negatively charged paper fibers, blocking the capillary pores between the fibers, thereby further increasing the water resistance of the paper. The silane coupling agent itself can also support the paper from the inside, thereby increasing the strength of the paper.

[0093] The harder styrene-methyl methacrylate copolymer core in the core-shell microspheres A serves as the system's skeleton and can be used to improve the ring crush strength of paper. The softer acrylate-acrylamide copolymer shell coated on the core surface can, on the one hand, reduce the brittleness of the paper caused by the addition of styrene. At the same time, it can also cross-link and entangle with the hydrophobic long-chain alkyl monomer and the silane coupling agent to form a dense network structure. The hydrophobic long-chain alkyl monomer itself can also react with the hydroxyl groups on the surface of the silane coupling agent to increase the dispersibility of the silane coupling agent in the system, thereby further enhancing the water resistance and ring crush strength of the paper.

[0094] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Within the scope of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0095] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A composite styrene-acrylic emulsion surface sizing agent, characterized in that: The surface sizing agent is prepared from the following raw materials in parts by weight: 20-30 parts of core-shell microspheres A, 10-15 parts of core-shell microspheres B, 3-5 parts of silane coupling agents, 8-12 parts of hydrophobic long-chain alkyl monomers, 2-4 parts of initiators, 2-5 parts of aluminum sulfate solutions, and 50-60 parts of deionized water; The ratio of the particle size of the core-shell microsphere A to the particle size of the core-shell microsphere B is 2-3:1; The core-shell microsphere A is a core-shell microsphere with styrene-methyl methacrylate copolymer as the core and butyl acrylate-acrylamide copolymer as the shell; The core-shell microspheres B are butyl acrylate-acrylamide copolymer microspheres; The preparation method of the core-shell microsphere A is as follows: Step A1. dissolving styrene, methyl acrylate, sodium dodecyl sulfate and nonylphenol oxyethylene ether in deionized water, pre-emulsifying by high-speed stirring at room temperature to obtain a core layer pre-emulsion, adding sodium bicarbonate and potassium persulfate, reacting at 75-80°C for 40-50 minutes to obtain a seed emulsion; Step A2. Dissolve butyl acrylate, acrylamide, sodium dodecyl sulfate and nonylphenol oxyethylene ether in deionized water, pre-emulsify with high-speed stirring at room temperature to obtain a shell pre-emulsion, then add sodium bicarbonate and potassium persulfate, and react at 70-75 ° C for 40-50 min; Step A3. The seed emulsion is heated to 75-80°C, and the shell pre-emulsion and potassium persulfate are added. After the addition is complete, triethanolamine is added to adjust the pH to 6.5-7.5, and the mixture is reacted at 75-80°C for 4-5 hours. The obtained suspension product is washed with 0.5 mol / L dilute hydrochloric acid for 3-5 times, and then washed with deionized water until neutral to obtain core-shell microspheres A; The preparation method of the core-shell microsphere B is as follows: Step B1. Dissolve sodium hydroxide and sodium chloride in deionized water to obtain phase A, and dissolve 1wt.% sodium dodecyl sulfate solution, magnesium chloride and sodium nitrite in deionized water to obtain phase B; Step B2. Phase B is added to phase A at a speed of 65-75 rpm by a peristaltic pump, and then 0.5 mol / L of dilute sulfuric acid solution is added to adjust the pH to 9.5-10.5 to obtain a magnesium hydroxide dispersion; Step B3. butyl acrylate, acrylamide, benzoyl peroxide and polyethylene glycol dimethacrylate are blended as phase C, phase C is added to the magnesium hydroxide dispersion, and homogenized with a high-speed shear emulsifier to obtain a stable suspension; Step B4. The suspension is reacted at 70-75°C for 15-20h, and then aged at 80°C for 1.5-2h. The obtained suspension product is washed with 0.5 mol / L dilute hydrochloric acid for 3-5 times, and then washed with deionized water until neutral to obtain core-shell microspheres B.

2. A composite styrene-acrylic emulsion surface sizing agent according to claim 1, characterized in that: The mass ratio of styrene, methyl acrylate, sodium dodecyl sulfate, nonylphenoloxyethylene ether, deionized water, sodium bicarbonate and potassium persulfate in step A1 is 2-3:1-1.25:1.5-2:0.8-1:140-150:0.4-0.5:0.5-0.

6.

3. A composite styrene-acrylic emulsion surface sizing agent according to claim 1, characterized in that: The mass ratio of butyl acrylate, acrylamide, sodium dodecyl sulfate, nonylphenoloxyethylene ether, deionized water, sodium bicarbonate and potassium persulfate in step A2 is 1-1.2:2-2.5:1.5-2:0.8-1.2:140-150:0.4-0.5:0.5-0.

6.

4. A composite styrene-acrylic emulsion surface sizing agent according to claim 1, characterized in that: The mass ratio of the seed emulsion, the shell pre-emulsion and potassium persulfate in step A3 is 10-15:10-15:0.8-1.

3.

5. A composite styrene-acrylic emulsion surface sizing agent according to claim 1, characterized in that: The mass ratio of sodium hydroxide, sodium chloride and deionized water in phase A described in step B1 is 1:1:10, the mass ratio of 1wt.% sodium dodecyl sulfate solution, magnesium chloride, sodium nitrite and deionized water in phase B described in step B1 is 2:1:1:10, the mass ratio of phase A and phase B described in step B2 is 1:1, and the mass ratio of butyl acrylate, acrylamide, benzoyl peroxide, polyethylene glycol dimethacrylate and magnesium hydroxide dispersion described in step B3 is 2-2.5:1.3-1.8:0.6-0.8:0.3-0.5:8-10.

6. A composite styrene-acrylic emulsion surface sizing agent according to claim 1, characterized in that: The silane coupling agent is any one of tetraethyl orthosilicate, methyltriethoxysilane and ethyltriethoxysilane, and the hydrophobic long-chain alkyl monomer is any one of octadecyl methacrylate, hexadecyl methacrylate and dodecyl methacrylate.

7. A composite styrene-acrylic emulsion surface sizing agent according to claim 1, characterized in that: The initiator is any one of benzoyl peroxide, potassium persulfate and ammonium persulfate, and the concentration of the aluminum sulfate solution is 35%-40%.

8. A composite styrene-acrylic emulsion surface sizing agent according to any one of claims 1 to 7, characterized in that: The preparation method of the surface sizing agent is as follows: Step S1. core-shell microsphere A, core-shell microsphere B, silane coupling agent, hydrophobic long-chain alkyl monomer, initiator and deionized water are uniformly mixed and reacted at 70-75° C. for 30-35 min to obtain a polymer emulsion; Step S2: adding aluminum sulfate solution to the polymer emulsion to obtain a composite styrene-acrylic emulsion surface sizing agent.

Citation Information

Cited By

  • Application of solid waste gypsum in papermaking

    CN122899084A